2020
DOI: 10.1016/j.reprotox.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Iodoacetic acid inhibits follicle growth and alters expression of genes that regulate apoptosis, the cell cycle, estrogen receptors, and ovarian steroidogenesis in mouse ovarian follicles

Abstract: The reactions between disinfectants and organic matter or inorganic matter in source water generates disinfection by-products (DBPs) such as iodoacetic acid (IAA). DBPs are associated with health effects such as bladder cancer and adverse reproductive outcomes, but the effects of IAA on the ovary are not well known. This study determined whether IAA exposure affects ovarian follicle growth, steroidogenesis, and expression of apoptotic factors, cell cycle regulators, estrogen receptors, and steroidogenic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…However, Kim et al found that IAA could inhibit the estrogenic activity of yeast cells . IAA also could inhibit the proliferation of mouse follicular cells in vitro and decrease sex steroid hormone levels by downregulating expression of Cyp17a1 , Hsd17b1 , and Cyp19a1 in steroidogenesis. , The discrepancies between our results and earlier studies may be associated with use of different end points, species of cells and animals, and in vivo and in vitro models.…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…However, Kim et al found that IAA could inhibit the estrogenic activity of yeast cells . IAA also could inhibit the proliferation of mouse follicular cells in vitro and decrease sex steroid hormone levels by downregulating expression of Cyp17a1 , Hsd17b1 , and Cyp19a1 in steroidogenesis. , The discrepancies between our results and earlier studies may be associated with use of different end points, species of cells and animals, and in vivo and in vitro models.…”
Section: Resultscontrasting
confidence: 92%
“…Previous quantitative structure–activity relationship (QSAR) analyses have predicted that IAA may have developmental toxicity, which could lead to developmental malformation of the neural tube in mice . IAA could inhibit the proliferation of mouse ovarian follicular cells in vitro and decrease the levels of estradiol, testosterone, and androstenedione by disrupting steroidogenesis. , IAA could also inhibit the estrogenic activity of yeast cells . Our previous results of the in vivo and in vitro experiments have shown that IAA has thyroid disrupting effects and decreases the ovary weight of rats .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In mice, iodoacetic acid inhibited antral follicle growth and reduced estradiol production by ovarian follicles in vitro [49]. To determine the mechanisms by which iodoacetic acid caused these alterations, Gonsioroski et al [50] analyzed the gene expression and sex steroid hormone levels of mouse ovarian follicles in vitro. They showed that iodoacetic acid dysregulated the expression of apoptotic factors, cell cycle regulators, steroidogenic factors, and estrogen receptors, subsequently disrupting cell proliferation and steroidogenesis [50].…”
Section: Non-human Animalsmentioning
confidence: 99%
“…To determine the mechanisms by which iodoacetic acid caused these alterations, Gonsioroski et al [50] analyzed the gene expression and sex steroid hormone levels of mouse ovarian follicles in vitro. They showed that iodoacetic acid dysregulated the expression of apoptotic factors, cell cycle regulators, steroidogenic factors, and estrogen receptors, subsequently disrupting cell proliferation and steroidogenesis [50]. Narotsky et al assessed the combined toxicity of regulated DBPs (TTHMs, HAAs, or TTHMs and HAAs) on the fertility indices of rats [51].…”
Section: Non-human Animalsmentioning
confidence: 99%